Emergency psychiatric nursing: A concept analysis - Pragholapati, Andria; Ismail, Suhartini (Utan Kayu Publishing, 2024)
Background: Individuals with Mental Disorders (ODGJ) are at risk of relapse, leading to emergencies. Untreated psychiatric emergencies can result in disability or even death. Emergency psychiatric care, if not promptly addressed, poses a crucial and complex topic. The aim of this research is to define and clarify these essential concepts, integrating them into mental health nursing care. Methods: Literature search employed keywords such as